Heterogeneous distribution of hepatitis B serological markers in rural areas of Mexico Distribución heterogénea de marcadores serológicos de hepatitis B en áreas rurales de México - Luis A Juárez-Figueroa; Felipe Javier Uribe-Salas; Carlos Jesús Conde-González (Instituto Nacional de Salud Pública, 2011)
OBJECTIVE: To study the distribution of the hepatitis B antibody (anti-HBc) based on a national serosurvey from 10 Mexican states showing a mean HBV prevalence higher than the national one. MATERIALS AND METHODS: This was a cross-sectional study. During 2003, anti-HBc was analyzed at INSP in 19 907 sera, and the related sociodemographic factors were determined. RESULTS: Anti-HBc prevalence was greater among men, but it was also associated to age, residence in a rural area, low socio-economic status, and illiteracy. Clusters of very high anti-HBc prevalence were found in several rural communities where the prevalence of anti-HBc in adults is 3 to 20 times the national average. CONCLUSIONS: Besides a low endemicity of HBV in Mexico, distribution is heterogeneous as was shown in several of the states studied, where there are rural towns with very high prevalence of HBV markers. National serosurveys are useful tools for identifying communities with hepatitis B hyperendemicity, where focused research and control measures are needed. OBJETIVO: Estudiar la distribución de anti-HBc en 10 estados con prevalencia mayor a la media nacional en la ENSA 2000. MATERIAL Y MÉTODOS: Durante 2003 se analizó en el INSP anti-HBc en 19 907 muestras de suero, se determinaron factores sociodemográficos relacionados. RESULTADOS: La prevalencia de anti-HBc fue mayor en hombres. Se asoció con la edad, residencia en áreas rurales, bajo nivel socioeconómico y analfabetismo. Se encontraron agrupamientos de alta prevalencia de anti-HBc en comunidades rurales en las cuales la prevalencia de anti-HBc en adultos está entre 3 y 20 veces por arriba de la media nacional. CONCLUSIONES: Contrastando con la baja endemicidad del VHB en México, su distribución es heterogénea. En varios estados se hallaron localidades rurales con muy alta prevalencia de anti-HBc. Las encuestas de salud permiten identificar comunidades donde la hepatitis B es hiperendémica y en las cuales se requiere enfocar la investigación y tomar medidas de control.